Hubungan Pemberian Air Susu Ibu (Asi) Eksklusif Dan Paparan Asap Rokok Terhadap Kejadian Pneumonia Pada Balita Di RSUD Labuang Baji Makassar Periode Juli 2018 – Juli 2019 - Andi Rara Pramei; Andi Tihardimanto; Syatirah Jalaluddin (Alami Journal (Alauddin Islamic Medical) Journal, 2022)
Pneumonia is an acute respiratory infection that is a health problem in the world because the mortality rate is very high in children under 5 years old (toddlers). The purpose of this study was to determine the relationship of exclusive breastfeeding and cigarette exposure with the incidence of pneumonia in infants in Labuang Baji Hospital Makassar in the period July 2018 - July 2019. This is an observational analytic study with a cross sectional approach. The method of sampling is a total sampling technique of 107 respondents. The data was collected by conducting interviews using questionnaires. The results showed that out of 112 samples, 48 toddlers (42.9%) were given exclusive breastfeeding and 64 toddlers (57.1%) were not exclusively breastfed. The majority of toddlers experiencing pneumonia in this study were exposed to cigarette smoke as many as 69 toddlers (61.6%). Conclusion: there is a significant relationship between exclusive breastfeeding and exposure to cigarette smoke with the incidence of pneumonia in toddlers. The suggestions are that it is hoped that health workers can educate mothers to give exclusive breastfeeding to their babies, carry out anti-smoking campaign programs and it is hoped that the community will play a role in reducing the incidence of pneumonia in toddlers by providing nutritious intake, exclusive breastfeeding and clean and healthy living behavior.